A Randomized Cross-Over Field Study of Pre-Hydration Strategies in Dogs Tracking in Hot Environments - Niedermeyer, Greta M.; Hare, Elizabeth; Brunker, Leslie K.; Berk, Richard A.; Kelsey, Kathleen M.; Darling, Tracy A.; Nord, Jess L.; Schmidt, Kasey K.; Otto, Cynthia M. (Frontiers in Veterinary Science, 2020)
The objective of this study was to evaluate 4 pre-exercise hydration strategies (oral water, chicken-flavored water, chicken-flavored oral electrolyte solution, and subcutaneous electrolyte solution) in working dogs conducting rigorous tracking operations in hot and arid conditions. In a randomized cross-over field study, 7 Border Patrol Search, Trauma, and Rescue (BORSTAR) Unit dogs working/training out of Fort Bliss in El Paso, Texas were randomly assigned to one of 4 different hydration strategy treatments each day for 4 days of study participation. Dogs were provided hydration treatment prior to running 2 separate one-mile tracks and were offered water while tracking. Body weight, blood, and urine were collected at the beginning of the study day and at the completion of each track. Core body temperatures were recorded using internal temperature sensing capsules. The impact of hydration strategy on change in weight, peak temperature, and serum chemical, hematological, and urinary parameters were analyzed using the COIN procedure in Ra. Compared to the other 3 hydration strategies, dogs receiving chicken-flavored water had higher blood creatine kinase values at the end of the second track (p=0.0361). Otherwise, hydration strategy had minimal effects on blood or urine parameters. Total fluid intake was lower with water only compared to the other three hydration strategies. Dogs developed elevated core body temperatures (median 41℃; 106℉) without signs of heat exhaustion or heat stroke. Alternate hydration strategies increased total fluid intake compared to water alone, however chicken-flavored water resulted in increased markers of muscle injury, suggesting electrolyte-enriched strategies may have an advantage as a hydration strategy. Additionally, electrolyte-enriched fluids before exercise may help these dogs maintain lower peak temperatures.